Implementing Quizizz as Game Based Learning and Assessment in the English Classroom - Rudi Irwansyah; Muna Izzati (UMBanjarmasin, 2021)
Quizizz is an online assessment tool as a fun multiplayer classroom activity that allows all students to practice together with their computer or Smartphone. The aim of this paper is to describe the implementation of Quizizz as a game based learning and assessment in the English classroom of SMA Negeri 1 Tamban Barito Kuala regency. There are 6 clasess learn English through this app during the COVID-19 pandemic. Quizziz is used for 20 minutes before finishing English class once the students feel very tired, sleepy, and getting bored for their English class. The teacher can easily make assessment using this application because the score directly showed at the report. Some of questions asked to those students regarding to their opinion of implementing Quizizz during the English class. The students feel excited and motivated doing the task because the display of the application very interesting like playing a game. According to testing the implementing of Quizizz by writer during the English skill classroom, found that all students were very active to answer the questions which provided by researches, and more concentrated on the topic. The findings shows that the students display the positive attitude for quizizz and become more motivated in learning English.